The Impact of Audit Elements on Tax Avoidance in China - Sun, Cheng-zhi (2022)
This paper examines the impact of audit factors on corporate tax avoidance in the Chinese context. By selecting a sample of 2,494 Chinese listed firms from the CSMAR database for the period 2011-2020 in the unique Chinese economic context, this paper finds that audit factors have a strong impact on tax avoidance. Among them, audit fees and audit opinions have a hindering effect on tax avoidance of Chinese firms, which are negatively related, while audit specialisation and audit rotation are facilitating effects on Chinese firms, which are positively related. In addition, this paper also verifies that ROA, leverage, firm size and corporate cash flow all have significant influences on corporate tax avoidance. The findings of this paper effectively complement the research in the Chinese tax avoidance literature and provide implications for stakeholders and regulators, as well as contributing to both the audit and tax avoidance fields.